Outcomes Following Extrahepatic and Intraportal Pancreatic Islet Transplantation: A Comparative Cohort Study - Verhoeff, Kevin; Marfil-Garza, Braulio A; Sandha, Gurpal; Cooper, David; Dajani, Khaled; Bigam, David L; Anderson, Blaire; Kin, Tatsuya; Lam, Anna; O'Gorman, Doug; Senior, Peter A; Ricordi, Camillo; et al. (Transplantation, 2022)
Preliminary studies show promise for extrahepatic islet transplantation (ITx). However, clinical comparisons with intraportal ITx outcomes remain limited. This single-center cohort study evaluates patients receiving extrahepatic or intraportal ITx between 1999 and 2018. Primary outcome was stimulated C-peptide level. Secondary outcomes were fasting plasma glucose, BETA-2 scores, and fasting C-peptide level. Multivariable logistic modeling evaluated factors independently associated with a composite variable of early graft failure and primary nonfunction within 60 d of ITx. Of 264 patients, 9 (3.5%) received extrahepatic ITx (gastric submucosal = 2, subcutaneous = 3, omental = 4). Group demographics were similar at baseline (age, body mass index, diabetes duration, and glycemic control). At 1-3 mo post-first infusion, patients receiving extrahepatic ITx had significantly lower stimulated C-peptide (0.05 nmol/L versus 1.2 nmol/L, P < 0.001), higher fasting plasma glucose (9.3 mmol/L versus 7.3 mmol/L, P < 0.001), and lower BETA-2 scores (0 versus 11.6, P < 0.001) and SUITO indices (1.5 versus 39.6, P < 0.001) compared with those receiving intraportal ITx. Subjects receiving extrahepatic grafts failed to produce median C-peptide ≥0.2 nmol/L within the first 60 d after transplant. Subsequent intraportal infusion following extrahepatic transplants achieved equivalent outcomes compared with patients receiving intraportal transplant alone. Extrahepatic ITx was independently associated with early graft failure/primary non-function (odds ratio 1.709, confidence interval 73.8-39 616.0, P < 0.001), whereas no other factors were independently predictive. Using current techniques, intraportal islet infusion remains the gold standard for clinical ITx, with superior engraftment, graft function, and glycemic outcomes compared with extrahepatic transplantation of human islets.